Computational biomechanics for medicine: measurements, models, and predictions - Nielsen, Poul M.F.; Wittek, Adam; Miller, Karol; Doyle, Barry; Joldes, Grand R.; Nash, Martyn P. (SpringerLink Bücher, 2019)
This volume comprises the latest developments in both fundamental science and patient-specific applications, discussing topics such as: cellular mechanics, injury biomechanics, biomechanics of the heart and vascular system, algorithms of computational biomechanics for medical image analysis, and both patient-specific fluid dynamics and solid mechanics simulations. With contributions from researchers world-wide, Computational Biomechanics for Medicine: Measurments, Models, and Predictions provides an opportunity for specialists in the field to present their latest methodologies and advancements